A Logistic Model for Counting Crowds and Flowing Particles - Weon, Byung Mook (Frontiers in Physics, 2020)
Counting how many people or particles pass through a specific space within a specific time is an interesting question in applied physics and social science. Here a logistic model is developed to estimate the total number of moving crowds or flowing particles. This model sheds light on a collective contribution of crowd or particle growth rate and transient probability within a specific space. This model may offer a basic concept to understand transport dynamics of moving crowds and flowing particles.